A Novel OnabotulinumtoxinA Treatment Technique to Obtain Predictable Outcomes in Eyebrow Position and Shape - Angelo-Khattar M (Dove Medical Press, 2020)
Maria Angelo-Khattar1,2 1American Academy of Anti-Aging Medicine (A4M), Dubai, United Arab Emirates; 2Shape Clinic, Kuwait City, KuwaitCorrespondence: Maria Angelo-KhattarAmerican Academy of Anti-Aging Medicine (A4M), Dubai, United Arab EmiratesTel +971506245494Email mkhattar@younatagroup.comBackground: OnabotulinumtoxinA has been approved for multiple clinical and dermatological indications. The toxin, produced by the bacterium Clostridium botulinum, is undoubtedly the most widely used cosmetic treatment for both the reduction and prophylaxis of wrinkles in the upper face and the reshaping of the eyebrows. However, the aesthetic outcomes obtained with respect to eyebrow position and shape are not always predictable and furthermore, untoward effects such as eyelid and brow ptosis are sometimes seen.Objective: This article suggests a novel injection technique of the upper face with OnabotulinumtoxinA to obtain predictable and reproducible results with respect to eyebrow position and shape, whilst greatly minimizing the risk of adverse effects such as brow and lid ptosis.Discussion: OnabotulinumtoxinA inhibits the release of acetylcholine and results in the temporary paralysis of skeletal muscle. The aesthetic outcome of wrinkle reduction typically lasts for a period of 14– 16 weeks. Although relatively safe in that the toxin does not have any irreversible side effects, even a temporary untoward reaction may be seriously distressing to the cosmetic patient.Conclusion: The proposed injection technique, when diligently followed, ensures that the final eyebrow position is pleasing and symmetrical with a negligible risk of any untoward effects.Keywords: botulinum toxin A, facial wrinkles, brow lift, treatment protocol